Botanical descriptors for Ricinus communis germplasm characterization obtained from different Costa Rica’s regions - Solera-Steller, Paola (2015)
Castor´s oil (Ricinus communis) is an oilseed plant. It´s used in various industries due to the high quality of its oil. Faced with the problem of the use of fossil fuels and growing needs to find alternative energy sources, castor´s oil shows high potential as a feedstock for biodiésel production. Countries like Brazil, Ecuador, Venezuela, Colombia and Mexico have been improving varieties of this specie presenting optimal levels of production and management research for industrialization. The major goal of this study was the evaluation and selection of botanical and morphological descriptors appropriated for germplasm characterization of Ricinus communis obtained from different country locations. Descriptive statistics analysis were performed including Principal Component Analysis (PCA) and Hierarchical Ascendant Classification (CJA) analysis of 28 morphological characters (vegetative and reproductive) from 50 accessions of castor´oil samples collected from nine Costa Rica’ life zones. The results showed significant statistics values for length of cluster and number of fruits per cluster, length/width ratio fruit, weight fruit, length/width ratio seed and weight seed, all these with higher correlations values (>45%). However, PCA showed high variability data, which is frequent among wild individuals; mainly due to their seed´s dispersion mechanisms and the diversity of the different collected areas. CJA showed three main groups ordered by correlations between size and number of fruits, length/ width ratio fruit, fruit weight, length/width ratio seed and seed weight, all these variables can be used as indicators for the castor´oil morphological characterization for this country.